ANALISIS INPUT OUTPUT SEKTOR PERTANIAN DI INDONESIA - , HANI PERWITASARI ([Yogyakarta] : Universitas Gadjah Mada, 2012)
research The purpose of this are: (1) to identify changes in the structure of Indonesia's economy, (2) to identify backward linkage and forward linkage between agriculture sector with other sectors in economic structure of Indonesia, (3) to know the multiplier effect of output, income, employment and gross value added of agriculture sector. The research analyzed Input-Output data, the domestic transactions based on producer price, that is classified 66 sectors published by the Central Statistics Agency (BPS) using Input-Output Analysis. in These results indicate that 1975 until 2008 the structure of Indonesia's economy has changed towards industrialization. Backward linkage and forward linkage between the agricultural sector with other sectors are under the average backward linkage and the forward linkage of economy all sector in Indonesia. Multiplier effect of output, income, employment in the agricultural sector are below the average of output multiplier effect, income, and employment sectors of the economy throughout Indonesia but the gross value added in above-average gross value added multiplier effects throughout the economy of Indonesia.